4(n-6)-(2-3n)=6n

Simple and best practice solution for 4(n-6)-(2-3n)=6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(n-6)-(2-3n)=6n equation:


Simplifying
4(n + -6) + -1(2 + -3n) = 6n

Reorder the terms:
4(-6 + n) + -1(2 + -3n) = 6n
(-6 * 4 + n * 4) + -1(2 + -3n) = 6n
(-24 + 4n) + -1(2 + -3n) = 6n
-24 + 4n + (2 * -1 + -3n * -1) = 6n
-24 + 4n + (-2 + 3n) = 6n

Reorder the terms:
-24 + -2 + 4n + 3n = 6n

Combine like terms: -24 + -2 = -26
-26 + 4n + 3n = 6n

Combine like terms: 4n + 3n = 7n
-26 + 7n = 6n

Solving
-26 + 7n = 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
-26 + 7n + -6n = 6n + -6n

Combine like terms: 7n + -6n = 1n
-26 + 1n = 6n + -6n

Combine like terms: 6n + -6n = 0
-26 + 1n = 0

Add '26' to each side of the equation.
-26 + 26 + 1n = 0 + 26

Combine like terms: -26 + 26 = 0
0 + 1n = 0 + 26
1n = 0 + 26

Combine like terms: 0 + 26 = 26
1n = 26

Divide each side by '1'.
n = 26

Simplifying
n = 26

See similar equations:

| 4x+1=34+7x | | (x-2)(x+6)=3x | | 3x+30=81 | | x^2+24x-112=0 | | -y=-x-4 | | b^2=2b | | t(t-7)=18 | | x^2-x+649=0 | | -2(x+5)+4x= | | -10-2x=x+5 | | y=x^2+3x-5 | | 10x-3x-9+3-x=18 | | 17x-8=12x+33 | | 4x-1=3x+4 | | 20t^2=64+64t | | 2x+7=4x+7 | | 4x^2-7x+13=6x+3 | | 5k-4k+6= | | 20t^2=64+64 | | 10+3y=-9 | | 6x^2-38x-80=0 | | -2c+12=2c-6+6c-12 | | -6x+8=14-3x | | b+b+b+6=6b+5-2b+9 | | y^2+7y-30=0 | | 4x-2=-2x-56 | | 7x-10=-37-2x | | 8k-6+3k-2k+3=4*33 | | 6-5x-2x=34 | | 6w^2+33w-18= | | 2d-8-5d=-3d-2d+6 | | 15=3.4n-2(n-4) |

Equations solver categories